(untitled) (Philippine Journal of Agricultural Economics, 2018)
The nutritional value of Pseudodiaptomus annandalie and its suitability as feed to milkfish larvae were determined. Pure isolates of P. annandalie was subjected to feeding in four different microalgal species (Chlorella sp., Chaetoceros calcitrans, Isochrysis galbana and Tetraselmis chuii) for 15 days of culture. Lipid extraction was done using Bligh and Dyer method and analyzed in a gas chromatograph for fatty acid profile. Results were analyzed using univariate ANOVA (p.0.05) and subsequent Tukey tests. Results of the first experiment showed that the number of fatty acids in P. annandalie varied significantly at different microalgal diets. DHA/EPA ratio was highest in Chaetoceros calcitrans (4.91%). This suggest that Chaetoceros calcitrans is the best microalgal food for P. annandalie because it promotes high DHA/EPA ratio in its fatty acid profile which is an important requirement for fish larvae. When live P. annandalie together with other natural foods were tested, results showed that treatment fed live copepods had significantly (p<0.05) higher average length after day 24 (14.86+0.78 mm) over other treatments. Survival rate was significantly highest in treatment fed live P. annandalie (65.58+0.65%) compared with other treatments. Live copepod therefore is a suitable feed for milkfish larvae because it contains a high fatty acid profile.